CULTURE-DEPENDENT APPROACHES AMONG THE CARIES PATHOGENS ISOLATED FROM THE CARIOUS DENTINE AND THEIR EMERGING DRUG RESISTANCE - LOHIYA, RUCHITA S.; INDUGU, NAGA NIMISHA; DEOTALE, VIJAYSHRI (International Journal of Current Pharmaceutical Research, 2023)
Objective: To evaluate the commonest caries pathogens from different type of caries andto screen for the emergence of drug resistance among the caries causing pathogenic bacteria. Methods: A cross-sectional study was conducted in the department of Microbiology. Sample Size was 44 and samples from carious dentine which was immediately transported to the microbiology laboratory. Samples were processed microbiologically to isolate the caries pathogens. Identification of strains were done by standard biochemical characterization studies. The isolates were subjected to antimicrobial sensitivity test. The results were recorded and analyzed for drug resistance. Results: Out of 44 patients, 40 aerobic bacteria, 2 anaerobic bacteria and 2 fungi were isolated. Out of the 40 aerobic bacteria, the most common isolated was Klebsiella pneumoniae followed by Pseudomonas spp. and Streptococcus viridians. Ciprofloxacin, Gentamycin and Linezolid showed excellent activity against Gram-positive Bacteria. The most frequently involved teeth of dental caries were mandibular 1st molar (54.54%) followed by Mandibular 2nd molar (13.63%). Conclusion: In our study we found that Klebsiella pneumoniae, Pseudomonas sp., Streptococcus viridians were the most frequent organisms encountered. The study implicates the need for time to time antimicrobial susceptibility examination of the dental caries pathogens that will help to prevent the emergence of resistance property among the dentinal pathogenic organisms.